PENGARUH PENERAPAN E-SAMSAT, TINGKAT EKONOMI, DAN BIRO JASA TERHADAP MOTIVASI MEMBAYAR PAJAK KENDARAAN BERMOTOR - Prasetyo, Haris; Herawati, Nurul; Auliyah, Robiatul (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
This research aims to examine the influence of implementing e-SAMSAT, economic level, and service bureau on motivation to pay motor vehicle tax during the COVID-19 pandemic. This research uses a sample of motor vehicle taxpayers in Jombang Regency, East Java Province. The number of respondents used was 107 motor vehicle taxpayers. The sampling method is simple random sampling. Data collection was carried out using a questionnaire method and processed using SPSS. The research methods used were pilot tests, descriptive statistical analysis, data quality tests, classical assumption tests, and multiple regression analysis. This research found that e-SAMSAT and economic level influenced motivation to pay motor vehicle tax during the COVID-19 pandemic. In contrast, service bureaus did not affect motivation to pay motor vehicle tax during the COVID-19 pandemic. The findings of this research imply that e-SAMSAT services can be an alternative in motivating taxpayer compliance in paying motor vehicle taxes. Therefore, it is necessary to intensify the socialization of e-SAMSAT services to motor vehicle taxpayers. The research implication related to economic-level findings is that the government needs to provide tax incentives to taxpayers if there is a problem of global economic difficulties, such as during COVID-19.